2010
DOI: 10.1039/c0cc03407j
|View full text |Cite
|
Sign up to set email alerts
|

A new class of rhodamine luminophores: design, syntheses and aggregation-induced emission enhancement

Abstract: A new class of rhodamine luminophores, 3',3''-bis(oxospiroisobenzofuran)-3,7-bis(dialkylamino)benzopyrano-xanthene derivatives (ABPX), have been successfully developed. The emission behavior of ABPX series is directly opposite to the concentration quenching of conventional rhodamine dyes. ABPX series exhibit aggregation-induced emission enhancement (AIEE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 23 publications
2
35
0
1
Order By: Relevance
“…

Fluorescent organic dyes have been widely used as biological materials such as bioprobes and biosensors. [4][5][6][7][8][9][10][11] Normally, the unusual emission can be observed in a water/organic solvent mixed system or in the solid state, in which the aggregation of nonfluorescent or weakly fluorescent dyes enhance the emission efficiency. In particular, red-light emission around 600-650 nm is visible to the naked eye.

…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…

Fluorescent organic dyes have been widely used as biological materials such as bioprobes and biosensors. [4][5][6][7][8][9][10][11] Normally, the unusual emission can be observed in a water/organic solvent mixed system or in the solid state, in which the aggregation of nonfluorescent or weakly fluorescent dyes enhance the emission efficiency. In particular, red-light emission around 600-650 nm is visible to the naked eye.

…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Normally, the unusual emission can be observed in a water/organic solvent mixed system or in the solid state, in which the aggregation of nonfluorescent or weakly fluorescent dyes enhance the emission efficiency. [4][5][6][7][8][9][10][11] Normally, the unusual emission can be observed in a water/organic solvent mixed system or in the solid state, in which the aggregation of nonfluorescent or weakly fluorescent dyes enhance the emission efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7] In our previous work, the protolytic equilibria of ABPX in various solvents were determined by spectrophotometric measurements and density functional theory calculations. [8] We found that ABPX01 could be categorized into three forms: a colorless species of the spirolactone form ABPX01 0 and two heterochromatic species of the monocationic form ABPX01H…”
mentioning
confidence: 99%
“…Aggregation is therefore the key of "photo-switching" in the on-off luminescent states. With this regard, the first rhodamine-based luminogen of bisbenzofuran-bisbenzopyrano-xanthene derivative [16] with AIE [17][18][19][20][21][22][23] properties was developed since its inherent rhodamine units can be easily in the confined, aggregated state.…”
Section: Introductionmentioning
confidence: 99%